Complex Band Structures and Lattice Dynamics of Bi2Te3‐Based Compounds and Solid Solutions. (26th April 2019) - Fang, Teng; Li, Xin; Hu, Chaoliang; Zhang, Qi; Yang, Jiong; Zhang, Wenqing; Zhao, Xinbing; Singh, David J.; Zhu, Tiejun
Abstract: Bi2 Te3 ‐based compounds and derivatives are milestone materials in the fields of thermoelectrics (TEs) and topological insulators (TIs). They have highly complex band structures and interesting lattice dynamics, which are favorable for high TE performance as well as strong spin orbit and band inversion underlying topological physics. This review presents rational calculations of properties related to TEs and provides theoretical guidance for improving the TE performance of Bi2 Te3 ‐based materials. Although the band structures of these TE materials have been studied theoretically and experimentally for many years, there remain many controversies on band characteristics, especially the locations of band extrema and the exact values of bandgaps. Here, the key factors in the theoretical investigations of Bi2 Te3, Bi2 Se3, Sb2 Te3, and their solid solutions are reviewed. The phonon spectra and lattice thermal conductivities of Bi2 Te3 ‐based materials are discussed. Electronic and phonon structures and TE transport calculations are discussed and reported in the context of better establishing computational parameters for these V2 VI3 ‐based materials. This review provides a useful guidance for analyzing and improving TE performance of Bi2 Te3 ‐based materials. Abstract : The key factors in the first‐principles calculations for (Bi1– x Sb x )2 (Te1– y Se y )3 are reviewed. Local‐density approximation is more accurate in the band structure calculations of relaxed Te‐based compounds due to the reasonable treatment in van der Waals force. The modified Becke–Johnson correction is needed for Bi2 Se3 .The low lattice thermal conductivities of Bi2 Te3 ‐based compounds are related to the low group velocity and lifetime.